Diagnostic application of magnetic islands rotation in JET. (3rd June 2016) - Buratti, P.; Alessi, E.; Baruzzo, M.; Casolari, A.; Giovannozzi, E.; Giroud, C.; Hawkes, N.; Menmuir, S.; Pucella, G.
Abstract: Measurements of the propagation frequency of magnetic islands in JET are compared with diamagnetic drift frequencies, in view of a possible diagnostic application to the determination of markers for the safety factor profile. Statistical analysis is performed for a database including many well-diagnosed plasma discharges. Propagation in the plasma frame, i.e. with subtractedE × B Doppler shift, results to be in the ion diamagnetic drift direction, with values ranging from 0.8 (for islands at the q = 2 resonant surface) to 1.8 (for more internal islands) times the ion diamagnetic drift frequency. The diagnostic potential of the assumption of island propagation at exactly the ion diamagnetic frequency is scrutinised. Rational- q locations obtained on the basis of this assumption are compared with the ones measured by equilibrium reconstruction including motional Stark effect measurements as constraints. Systematic shifts and standard deviations are determined for islands with (poloidal, toroidal) periodicity indexes of (2, 1), (3, 2), (4, 3) and (5, 3) and possible diagnostic applications are indicated.